2018
DOI: 10.1108/ijhcqa-07-2017-0137
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting sentinel events in hospital emergency department: a qualitative study

Abstract: Purpose A sentinel event is an unexpected occurrence resulting in death or serious physical or psychological injury or the risk thereof. The purpose of this paper is to investigate the influencing factors of sentinel events in the emergency department of a military hospital in Tehran to find out some of the effective solutions. Design/methodology/approach In this qualitative study with content analysis approach, 20 hospital healthcare personnel participated as participants from the fields of medicine and nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The documents have shown that the use of the ESI triage system and the division of work shifts per day will lead to improved job potential and increased satisfaction of clients (Tatli et al, 2018). Studies have indicated that lack of human resources, lack of expert human resources and absence of basic rules are some of the important factors in the development of events in the emergency department (Zaboli, Malmoon, Soltani‐Zarandi, & Hassani, 2018). The results proved that some of the main causes of unwanted incidents in the emergency room are the lack of timely access to individuals and professionals, unavailability of up‐to‐date and appropriate instructions, the absence of a team aware of all regulations, the absence of adequate or on‐call staff for use at work pressures, the absence of standard equipment for identifying and preventing potential hazards, and the absence of updated equipment to increase prognosis at incident time (Davoodi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The documents have shown that the use of the ESI triage system and the division of work shifts per day will lead to improved job potential and increased satisfaction of clients (Tatli et al, 2018). Studies have indicated that lack of human resources, lack of expert human resources and absence of basic rules are some of the important factors in the development of events in the emergency department (Zaboli, Malmoon, Soltani‐Zarandi, & Hassani, 2018). The results proved that some of the main causes of unwanted incidents in the emergency room are the lack of timely access to individuals and professionals, unavailability of up‐to‐date and appropriate instructions, the absence of a team aware of all regulations, the absence of adequate or on‐call staff for use at work pressures, the absence of standard equipment for identifying and preventing potential hazards, and the absence of updated equipment to increase prognosis at incident time (Davoodi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One of the leading structural factors in dropping the quality of care is the lack of supplies and equipment. Evidence has revealed that the structural factors such as the upgrading of medical equipment affect the quality of the emergency structure (Zaboli et al, 2018; Zaboli, Shokri, Javadi, Teymourzadeh, & Ameryoun, 2016). The results of the studies showed that the major shortage of equipment in the emergency structure is effective (Kotsiou, Srivastava, Kotsios, Exadaktylos, & Gourgoulianis, 2018) and the shortage of basic equipment leads to delays in triage and adverse outcomes, misconceptions and inappropriate decisions (Aloyce, Leshabari, & Brysiewicz, 2014; Fry & Burr, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal tersebut dapat menimbulkan bahaya bagi pasien bahkan berkontribusi dalam peningkatan kematian pasien (Saleem et al, 2015). Bahaya-bahaya yang muncul sebagian besar terjadi karena kurang efektifnya komunikasi antar petugas medis maupun tenaga kesehatan lainnya (Zaboli et al, 2018). Penelitian lain juga menunjukan bahwa pelaksanaan handover yang baik berdampak pada baiknya pengelolaan obat oleh perawat selama masa pandemic Covid-19.…”
Section: Pendahuluanunclassified